Titik Temu Kesejarahan Alquran antara Kesarjanaan Timur dan Barat; Perbandingan Penafsiran Darwazah dan Dilthey - Cholid Ma'arif (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
Attempts to historicize the Koran have been carried out by many Muslim scholars through a set of nuzuli interpretations. In the same breath, the Western perspective gives rise to an analysis of historical hermeneutics, one of which is represented by the hermeneutical thought of Wilhelm Dilthey. This study examines the Historical Meeting Points of the Qur'an between Eastern and Western Scholars; Comparison between Muhammad Izzat Darwazah's nuzuli interpretation of thought and Wilhelm Dilthey's historical hermeneutics. Researchers used a qualitative approach based on literature studies. The results of the research show that there are several findings as follows: 1) there are six points of contact between Darwazah and Dilthey's thinking on aspects; orientation, object relations, methods of interpretation, deepening of concepts, involving elements of language, and foundation of application. 2) of the six points of contact, there are three points of similarity and three other points of difference which can still support each other in a more comprehensive historical interpretation structure. The results of these findings can at least serve as an introduction to reforming the historical-based interpretation of the Koran into an integrated methodology that is more scientifically integrative. Keywords: Interpretation, History, Intersection, Darwazah, Dilthey.